Special Interest Tourism Development at Tongaci Beach Tourism, Sungailiat, Bangka Belitung - Ruth Soesanto; Budi Setiawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The tourism sector is one of the largest and strongest sectors in the world economy and is one of the main drivers of the world economy which is able to provide quite a large amount of foreign exchange for the country. One of the fastest growing tourism sectors in the tourism industry is special interest tourism which shows that tourists are starting to demand more varied and stimulating holiday experiences. The aim of this research is to develop special interest tourism in the form of Hatchlings Babel Sea Turtle Conservation in Bangka Belitung which is a conservation site to maintain and minimize the decline in turtle populations, especially in Bangka Belitung waters. The method used in this research is a qualitative method where the data obtained is by conducting direct observations and interviews at the Babel Tukik Conservation. Hatchlings Babel Sea Turtle Conservation is also used as a special interest tourism facility as well as an educational place so that local people and foreign tourists can get to know more about sea turtles and it is hoped that awareness will arise to preserve sea turtles from the threat of extinction and damage to the marine ecosystem due to sea tin mining and illegal hunting